Impact of Industry 4.0 on the economy and production - T. V. Mezina; A. V. Zozulya; P. V. Zozulya; T. F. Chernova; A. V. Pletnyova (Вестник университета)
The difficulties and problems faced by economic entities, countries and regions, in general, on the way to implementing the achievements and developments of Industry 4.0 have been designated in the article. Special attention has been paid to economic and production aspects, as well as changes in the relevant systems in the context of radical technological transformations. In particular, it has been established that markets are becoming oligopolistic, the role and importance of medium and small businesses is significantly increasing, the problems of social inequality and tension in connection with growing unemployment and the need for highly qualified personnel are becoming more acute. In addition, the features of competition for technologies, investments, sales markets, territories of productive forces location have been highlighted. Attention has also been focused on the main “revolutionary” trends in industrial development associated with the launch of the innovation and technological cycle initiated by “Industry 4.0”. Specific actions and measures have been identified to implement these trends into reality.